2018
DOI: 10.1039/c8ob01596a
|View full text |Cite
|
Sign up to set email alerts
|

H- and J-aggregates formed from a nontraditional π-gelator depending on the solvent polarity for the detection of amine vapors

Abstract: A difluoroboron β-diketonate complex can self-assemble into H- and J-aggregates in the solvents with different polarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…[1c] It was also found that the strong emission of TCbzBSF in xerogel‐based film could be quenched obviously when exposed to the vapors of aniline, N ‐methylaniline and N , N ‐ dimethylaniline. Notably, the detection limit for aniline vapor of the film was as low as 0.56 ppb, exhibiting higher performance than the other reported sensors …”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…[1c] It was also found that the strong emission of TCbzBSF in xerogel‐based film could be quenched obviously when exposed to the vapors of aniline, N ‐methylaniline and N , N ‐ dimethylaniline. Notably, the detection limit for aniline vapor of the film was as low as 0.56 ppb, exhibiting higher performance than the other reported sensors …”
Section: Introductionmentioning
confidence: 64%
“…We observed the linear relationship between 1‐I/I 0 and the concentration of aniline, and the detection limit was as low as 0.56 ppb, which was lower than the reported sensors . We deemed that the high specific surface areas of the nanofibers and the large space in 3D networks would be helpful for the high performance of the xerogel‐based film in the fluorescent responsive to aniline . The fluorescence emission and UV/Vis absorption spectral titration results were gained in tetrachlormethane to reveal the fluorescence sensory mechanism of TCbzBSF in the film towards gaseous aniline.…”
Section: Resultsmentioning
confidence: 89%
“…Intermolecular π-π stacking and non-covalent bonding FIGURE 1 | Gelation of boron-difluoride compounds on the basis of the effect of solvent, molecular structure, effect of substituents and intermolecular interactions. Reproduced with permission from Sun et al, 2018Sun et al, , copyright 2018 Royal Society of Chemistry. Reproduced from Naim et al, 2021, copyright 2021 American Chemical Society.…”
Section: Self-assembly Into Gelsmentioning
confidence: 99%
“…Reproduced with permission from Mi et al, 2018 , copyright 2018 Royal Society of Chemistry. Reproduced with permission from Sun et al, 2017 , copyright 2017 Royal Society of Chemistry. Reproduced with permission from Wang et al, 2017 , copyright 2017 WILEY-VCH.…”
Section: Self-assembly Into Gelsmentioning
confidence: 99%
See 1 more Smart Citation